2013
DOI: 10.1177/1756283x13498661
|View full text |Cite
|
Sign up to set email alerts
|

Screening colonoscopy bowel preparation: experience in an urban minority population

Abstract: Methods: Suboptimal bowel preparation, present in over 20% of colonoscopies, can severely compromise the effectiveness of the colonoscopy procedure. We surveyed 93 primarily urban minority men and women who underwent asymptomatic 'screening' colonoscopy regarding their precolonoscopy bowel-preparation experience. Results: Print materials alone (39.8%) and in-person verbal instructions alone (35.5%) were reportedly the most common modes of instruction from the gastroenterologists. Liquidcontaining laxative (70.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Screening for cancer can reduce incidence of and/or death from cancer by detecting an early preclinical disease. Indeed, patients with colorectal cancer who are diagnosed through screening or at early stages have a better chance of surviving than those diagnosed after developing symptoms (7,19). Therefore, it is of critical importance to enhance public awareness about the importance of engagement in cancer screening practices in the absence of symptoms.…”
Section: Cancer Screeningmentioning
confidence: 99%
See 1 more Smart Citation
“…Screening for cancer can reduce incidence of and/or death from cancer by detecting an early preclinical disease. Indeed, patients with colorectal cancer who are diagnosed through screening or at early stages have a better chance of surviving than those diagnosed after developing symptoms (7,19). Therefore, it is of critical importance to enhance public awareness about the importance of engagement in cancer screening practices in the absence of symptoms.…”
Section: Cancer Screeningmentioning
confidence: 99%
“…Some non-modifiable risk factors for colorectal cancer include age, ethnic background, and the presence of specific diseases or syndromes. Colorectal cancer can affect young adults, yet the chances increase significantly after the age of 50 (7,8). Personal history of colorectal polyps, inflammatory bowel diseases, or type II diabetes mellitus also increase the chance for developing cancers in the colon and rectum (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the existence of these recommendations, rates of CRC screening in general and colonoscopy screening in particular are less than optimal [5] . One reason for this may be that preparing for a colonoscopy is typically considered the "worst part" of the colonoscopy procedure [6] . Inadequate bowel preparation, which has been shown to occur in as many as 20% of colonoscopies [7] , can obscure vision, and pre-cancerous or cancerous polyps can be missed [7,8] .…”
Section: Clinical Trials Studymentioning
confidence: 99%
“…In this study most of the subjects were female (72%) with mean age of 47.76 years old. The majority of the patients who underwent colonoscopy from study by Basch, et al 11 showed similar demographic characteristics. Most of the subjects were female (80.6%) with mean age 59.8 years.…”
Section: Discussionmentioning
confidence: 85%